THE EFFECT OF PLANT GROWTH REGULATORS TYPE IN TRADE MARK AND GROWING MEDIUM ON GROWTH OF WATER APPLE CITRA CUTTINGS (Syzygium aqueum Burm.f. Alston) - Tria R Anggraeni; Ellen R. Sasmita; Rina Srilestari (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
Water apple citra is a local fruit that contains a complete mineral. Production of water apple citra can be increased through vegetative propagation, one of them is cuttings. The growth of cuttings can be stimulated using plant growth regulators and growing medium. This study aims to determine the effect of plant growth regulators type and growing medium as well as the interaction between these factors. The research was conducted on March until May 2016 at the garden experiment, Faculty of Agriculture, UPN “Veteran” Yogyakarta. This research used Randomize Completely Block Design (RCBD) factorial pattern with three replications. There were two factors studied, the first factor was the type of plant growth regulators consist of root-up, rootone–F, atonic and without plant growth regulatos, the second factor was growing medium consist of the river sand, floral foam, and river sand+compost. The observed data were analyzed by analysis of variance (ANOVA) and continued by DMRT at 5% real level. The results showed that rootone-F could increase percentage of cutting life and root length. Growing medium of river sand+compost could increase percentage of cutting life. There were an interaction due to the combination of treatment on the observation variable such as root length and root volume.was analyzed by using Duncan Multiple Range Test (DMRT) at 5% level. The result showed that there were an interaction between liquid organic fertilizer various and Trichoderma sp. on the plant height at 42 days (the days after planting), the leaves number at 42 days (the days after planting), the root lenght, the roots number, and the crop weight of red cabbage. The treatment combination of cow urine and Trichoderma sp. gave the best crop weight compared to other treatments. There was no significant effect on vitamin C and vitamin A content in the red cabbage.Keyword: water apple citra, plant growth regulators, growing medium